Place and nature essays in Russian environmental history - Moon, David, 1959-; Breyfogle, Nicholas B., 1968-; Bekasova, Alexandra (Cambridgeshire : White Horse Press, 2021)
This book offers new perspectives on the environmental history of lands that have come under Russian and Soviet rule by paying attention to 'place' and 'nature' in the intersection between humans and the environments that surround them.
eBooks on EBSCOhost
Keywords: Human ecology -- Russia, Northwestern; Nature and civilization -- Russia, Northwestern; Russia, Northwestern -- Environmental conditions; Nature -- Effect of human beings on -- Russia, Northwestern -- History; Écologie humaine -- Russie (Nord-Ouest); Nature et civilisation -- Russie (Nord-Ouest); Êtres humains -- Influence sur la nature -- Russie (Nord-Ouest) -- Histoire; Russie (Nord-Ouest) -- Conditions environnementales; Ecology; Human ecology; Nature and civilization; Nature -- Effect of human beings on; Northwestern Russia; History